THE CONTENT OF OUT-OF-SCHOOL EDUCATION IN THE CONTEXT OF WAR TIME AND POST-WAR RECONSTRUCTION IN UKRAINE - Lytovchenko, Olena (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The article presents the results of the analysis of the features of the content of out-of-school education in the context of wartime and post-war reconstruction of Ukraine. It has been updated that out-of-school education is an integral component of the education system of Ukraine, defined by the Constitution of Ukraine, the Laws of Ukraine “On Education”, and “On Out-of-School Education”. Currently, the Law of Ukraine “On Out-of-School Education” is being updated considering the country’s current situation, social requests, etc. The materials of the article highlight the analysis of the context of the development of the content of out-of-school education such as the challenges of wartime, in particular, based on the results of monitoring studies of education in Ukraine in 2022-2023, analytical materials of state centers of out-of-school education; analysis of the results of the survey of teachers of out-of-school education institutions; the foundations and the most relevant vectors in the implementation of the content of out-of-school education are defined. The main research methods are defined as theoretical analysis of the provisions of scientific publications, analysis of normative documents, analytical references; an online survey of teachers of out-of-school education institutions; analysis of the experience of institutions of out-of-school education in order to determine the state of the problem in educational practice; generalization and systematization of data. The context in which the content of out-of-school education is developed is summarized, emphasizing the following challenges of wartime: challenges in the humanitarian sphere. “Families and children who have been forced to leave their homes often have traumatic experiences, feel anxious, and need psychosocial support” (UNICEF. Humanitarian Situation Report No. 24); as a result of military actions on the territory of Ukraine, out-of-school education institutions were destroyed and damaged; a significant number of children and school youth lost access to quality education and others. The most relevant vectors in the implementation of the content of out-of-school education in the conditions of wartime and post-war reconstruction have been determined: the creation of a safe educational environment; implementation of the principle of national orientation, construction of the educational process based on Ukrainian national values, development of the Ukrainian-speaking environment; creation of conditions for awareness of belonging to the European community; development of an inclusive and barrier-free educational environment, provision of socio-pedagogical and psychosocial support to all participants of the educational process.